Analysis of E-Commerce data breach and theft - Adawiyah, Rodiatun; Prasetyo, Muhammad Arif; Ayu, Hanuring; Septiyan, Raymond; Leonardy, Steven; Calvin, Michael (Priviet Social Sciences Journal, 2022)
The development in the field of E-commerce is something that is very important for our country today. E-commerce is not only advancing the country in the field of electronics, but this development can also be felt in other fields such as: Economics, and also the field of Education. However, it is not the only benefit that we can feel from these developments. There are things that can be very detrimental to us if we are not careful enough in the development of this E-commerce technology. Oneaofatheamostaimportant thingsato watch outafor is the breach of individual data/identity leakage that can be carried out by irresponsible parties in the E-commerce sector. Even though there are already articles of the ITE Law Article 32 Paragraphs 1, 2, and 3 which regulate the theft of personal data, the crime of theft still occurs in Indonesia. We can see examples of this crime from several similar crime cases, such as: The case of data leakage of 91 million accounts on Tokopedia in May 2020 and the case of data leakage of Cermati and Lazada involving 2.9 million accounts at the end of 2020.